Scoping an integrated ecosystem assessment for South Africa - Skein, Lisa; Sink, Kerry J.; Majiedt, Prideel A.; van der Bank, Megan G.; Smit, Kaylee P.; Shannon, Lynne J. (Frontiers in Marine Science, 2022)
The need to move toward marine ecosystem-based management is globally recognized. Few countries effectively account for multiple interacting pressures in their marine assessments, planning and management. Many socio-economic sectors currently operate in South African waters and in most cases, their associated pressures are managed on a sector-by-sector basis and interacting pressures are seldom accounted for in assessments or decision-making. For ecosystem-based management to be effective, a science-based approach to prioritize sectors and pressures needing most urgent action, and to identify affected ecological components is needed. Integrated Ecosystem Assessment (IEA) has hence been put forward as a tool that can organize relevant information and provide context for cross-sectoral management decisions. Consisting of five main stages that form an iterative cycle, the first IEA stage involves scoping of top management priorities in a given area and can be done by way of risk assessment. Through the ODEMM (Options for Delivering Ecosystem-based Marine Management) approach, linkage chains (interactions) among sectors, pressures and affected ecological components for the entirety of the South African marine territory were identified. Subsequently, impact risk scores of each linkage chain were calculated based on the exposure and severity of impacts faced by ecological components from pressures that are associated with each sector. Fishing was the sector with the greatest connectivity (11.65% proportional connectance) in the framework and ranked highest in terms of impact risk (summed), followed by Shipping and Coastal infrastructure. Pressures with the most serious impacts on ecological components, as identified through summed impact risk scores, included Bycatch, Species extraction, and Incidental loss and the ecological components most affected were those primarily associated with Fishing and its associated pressures. These findings align with those of the recent South African National Biodiversity Assessment and corroborate views of local stakeholders. This study also identified key local knowledge gaps, including impacts of underwater noise, invasive species, and climate change, that must be better understood to improve assessment accuracy and guide management prioritization of pressures exerted by most impactful sectors.